Bovine leptospirosis and its importance in one health: an integrative review (Research, Society and Development, 2022)
Leptospirosis is a zoonosis with a worldwide distribution. In cattle, the disease results in serious losses for rural producers and for the economy of the affected countries. In addition to the economic impact, bovine leptospirosis is considered an occupational risk factor, highlighting the relevance of leptospirosis in the context of one health. The objective of this integrative review was to discuss the importance of bovine leptospirosis in Brazil and the world within the context of one health. The work was carried out between August and November 2021. The search was performed in the MedLine, SciELO and VHL databases. The descriptors used were: Leptospirosis; beef; occupational. The use of descriptors in the databases allowed the search for 118 articles, which were published in languages such as Portuguese, English, Spanish, Polish, Dutch, Russian, German and French, between 1961 and 2021. After the application of the Inclusion and exclusion criteria were selected 53 articles for text analysis. Through the analysis of the prevalence and incidence rates of published works, it can be shown that bovine leptospirosis can be considered an endemic disease in all continents of the world. It can also be observed that occupational activities related to cattle on farms and in industry pose a high risk for human leptospirosis. Thus, it is expected that this review will alert to the importance of bovine leptospirosis in the context of single health and, thus, that this study will serve as a reference for future studies on this topic.